KEWENANGAN NOTARIS DALAM PEMBUATAN SURAT KETERANGAN WARIS UNTUK WARGA NEGARA INDONESIA - I Gusti Kade Prabawa Maha Yoga; Afifah Kusumadara; Endang Sri Kawuryan (Universitas Negeri Malang, 2018)
The purpose of this article is to discuss the authority of the notary in making a certificate of inheritance and legal force for the certificate of inheritance for Indonesian citizens after the enactment of Law Number 24 of 2013 concerning Population Administration. The study uses a normative juridical method with a legislative approach and analytical approach. The legislative approach is used to analyze problems caused by inconsistencies in norms of the relevant laws and regulations in making a certificate of inheritance. The analytical approach is used to analyze the meaning contained in the terms used in legislation regarding the drafting of a certificate of inherit- ance conceptually. Notaries have strong authority in making certificate of inheritance for Indonesian citizens without discriminating between population groups. The certificate of inheritance made by a Notary has perfect legal force.